ASSESSMENT OF THE OSMO-CONVECTIVE DEHYDRATION ON THE QUALITY ATTRIBUTES AND CENTESIMAL COMPOSITION OF YACON (Smallanthus sonchifolius) - PERUSSELLO, CAMILA AUGUSTO; MARIANA, VIVIANA COCCO; MASSON, MARIA LÚCIA; DE CASTILHO, FERNANDA (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2013)
This work has studied the application of the osmo-convective dehydration on yacon roots, regarding its composition and quality attributes. Slices of yacon were submitted to osmotic treatment with sucralose solution followed by convective dry. The experiments followed a complete 23 factorial design to assessthe effect of three variables of the process (temperature, stirring rate of the osmotic solution and drying temperature) over four quality attributes (moisture content, color, luminosity and soluble solid content). The application of the osmotic treatment before convective drying provided quality gains to the dried product, such as low browning and shrinkage rates, and reduction of the structural damages towards angular distortions and fissures, in comparison to the samples dried directly on the tray dryer. The effect of osmotic treatment over the centesimal composition of yacon have resulted on absorption of sucralose and water loss without a significance compromise of its nutritional attributes. The obtained product presented different contents of moisture, but similar levels of darkening and color alteration at diverse experimental conditions.